The Effect of Supplier Collaboration, Transport Efficiency, Technology Adoption, and Market Demand on Distribution Efficiency and Profitability of Pumpkin Seed Supply Chain in Indonesia - Haryono Haryono; Indah Epriliati; Mochammad Muchid; Eko Prasetyo; Budi Endarto (Westscience Press, 2024)
This study examines the effects of supplier collaboration, transportation efficiency, technology adoption, and market demand on the distribution efficiency and profitability of the pumpkin seed supply chain in Indonesia. Using a quantitative approach, data were collected from 150 respondents involved in the supply chain, including suppliers, distributors, and logistics providers. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that supplier collaboration, transportation efficiency, and technology adoption significantly enhance distribution efficiency, which in turn positively impacts profitability. Market demand was also found to moderate the relationship between distribution efficiency and profitability, particularly during periods of high demand. These findings underscore the importance of fostering collaboration, optimizing transportation, and adopting technology to improve the supply chain’s operational performance and financial outcomes. The study provides valuable insights for practitioners and policymakers aiming to enhance the agricultural supply chain's competitiveness and sustainability in Indonesia.